Pay regulation – is more better?. Issue 1 (2nd January 2021) - Chu, Jenny; Gupta, Aditi; Livne, Gilad
Abstract : From October 2013, UK law and regulations (the Reform ) require periodic binding shareholders' approval of executive directors' remuneration policy, as well as enhanced disclosure in remuneration reports. These requirements supplement an ongoing requirement for an annual non-binding vote on compensation outcomes that are detailed in the remuneration report. Using a large sample of listed companies from 2010–2017 we investigate whether the Reform has affected pay levels, pay-performance sensitivity, the pay gap between the CEO and other employees, the amount of cash returned to shareholders, and dissent voting on the remuneration report. We find little evidence that the Reform has affected these variables in our sample firms. Using market-based tests we find that market participants anticipated an improvement in corporate governance for some key dates before the Reform came into force. Taken together, the paper's evidence suggests the Reform has not met its stated objectives.